Promoting nutrition-sensitive potato value chains in Kenya. Project profile. - International Potato Center (International Potato Center, 2019)
Potato has underexploited potential to contribute to food security and incomes among Kenyan smallholders. This project builds on the past work of the International Potato Center (CIP) to increase the current low levels of productivity. It focuses on building the skills of farmers and other stakeholders to apply good agricultural practices and increase the availability of quality planting materials.